A new species of genus Falsoibidion Pic, 1922 (Coleoptera: Cerambycidae: Cerambycinae) from Hubei, China - Wang, Ping; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2020)
The genus Falsoibidion Pic, 1922 (Cerambycidae: Cerambyinae: Callidiopini) was established based on an Oriental species Falsoibidion fasciatum Pic, 1922 from Vietnam.